2001
DOI: 10.1161/hy1201.101214
|View full text |Cite
|
Sign up to set email alerts
|

History About the Discovery of the Renin-Angiotensin System

Abstract: Abstract-The history of the discovery of the renin-angiotensin system began in 1898 with the studies made by Tigerstedt and Bergman, who reported the pressor effect of renal extracts; they named the renal substance renin based on its origin. In 1934, Harry Goldblatt induced experimental hypertension in dogs by clamping a renal artery. About 1936, simultaneously in the Medical School of the University of Buenos Aires, Argentina, and in the Eli-Lilly Laboratories in Indianapolis, 2 independent groups of research… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
110
0
10

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 208 publications
(131 citation statements)
references
References 29 publications
(18 reference statements)
1
110
0
10
Order By: Relevance
“…The marked vasopressor effects of angiotensin were noted soon after its first isolation in the late 1930s, 16,17 and case reports have described the successful use of various bovine and human angiotensin II formulations as rescue therapy for patients with refractory shock. [18][19][20] The potential usefulness of angiotensin II as a vasopressor is also supported by a small pilot study.…”
Section: Discussionmentioning
confidence: 99%
“…The marked vasopressor effects of angiotensin were noted soon after its first isolation in the late 1930s, 16,17 and case reports have described the successful use of various bovine and human angiotensin II formulations as rescue therapy for patients with refractory shock. [18][19][20] The potential usefulness of angiotensin II as a vasopressor is also supported by a small pilot study.…”
Section: Discussionmentioning
confidence: 99%
“…Reduction in renal perfusion pressure activates multiple pressor systems, including the renin-angiotensin system 22 and renal adrenergic nerves. 23 When detected and treated soon after vascular occlusion, as in the case of vessel dissection or occlusion by an aortic stent graft, restoring blood flow can reverse this process and systemic hypertension, often without evident injury to the kidney.…”
Section: Tissue Damage Within the Poststenotic Kidneymentioning
confidence: 99%
“…Following enzymatic conversion of angiotensin 1 into angiotensin 2 (inhibited by ACE inhibitors), the latter exerts complex cardiovascular actions, including sympathoexcitation [2]. Studies have shown that increased activity of the sympathetic nervous system (SNS) can alter human sleep.…”
Section: Sns Sympathetic Nervous System Sws Slow-wave Sleepmentioning
confidence: 99%